2003
DOI: 10.1002/uog.39
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound fetal lung volume measurement: a systematic study comparing the multiplanar method with the rotational (VOCAL) technique

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
3
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 19 publications
4
122
3
9
Order By: Relevance
“…These findings suggest that fetal RVs do not differ in ethnically different populations and that both 3D-US volumetric methods produce similar results. In a previous publication on lung volume estimation in fetuses at risk for lung hypoplasia, Kalache et al [24] reported that the VOCAL method with a 30° rotation and the multiplanar method also yielded similar results.…”
Section: Discussionsupporting
confidence: 57%
“…These findings suggest that fetal RVs do not differ in ethnically different populations and that both 3D-US volumetric methods produce similar results. In a previous publication on lung volume estimation in fetuses at risk for lung hypoplasia, Kalache et al [24] reported that the VOCAL method with a 30° rotation and the multiplanar method also yielded similar results.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have shown the clinical applicability of 3DUS to estimate fetal organs such as the liver, 13,14 lungs, 15,16 brain, 17 and limbs. 18 Raine-Fenning et al 19 compared the in vitro validity and reliability of different 3DUS methods in the assessment of volumes and reported that the multiplanar and VOCAL methods yielded similar results, although the rotational VOCAL was superior to the multiplanar method for irregularly shaped objects.…”
Section: Discussionmentioning
confidence: 99%
“…These include the planimetric, prolate ellipsoid volume, and ellipsoid volume measurement methods [13] . The accuracy of sonographic estimates of STV can be affected by several factors [19,20] , including the number of slices taken, the experience of the sonographer, intraobserver and interobserver variability, software, and image resolution and acquisition rates of the sonographic device. Comparison of methods has shown that both two-and three-dimensional techniques tend to underestimate the true volume [19] .…”
Section: Discussionmentioning
confidence: 99%